Chemiluminescence molecular probe with a linear chain reaction amplification mechanism. Issue 6 (24th January 2019) - Gnaim, Samer; Shabat, Doron
Abstract : A new signal amplification probe with a linear chain reaction amplification mechanism and distinct chemiluminescence output was developed. Abstract : A new signal amplification probe with a linear chain reaction amplification mechanism and distinct chemiluminescence output was developed. The probe is composed of a unique structural motif that combines a chemiexcitation mechanism with an intramolecular transesterification into a single molecular structure. As demonstrated with a probe designed to detect hydrogen peroxide, an auto-inductive chemiluminescence signal amplification was obtained through methanol release by an intramolecular transesterification of the generated 2-hydroxymethylbenzoate derivative. The methanol was then oxidized by alcohol oxidase to regenerate the analyte of interest, hydrogen peroxide. Our probe enabled direct measurement of light emission with a limit of detection of 2.5 μM, whilst the assay was rapidly completed within 14 to 150 minutes. Such molecular probes with chemiluminescence signal enhancement through analyte amplification could be used for the detection of other chemical and biological analytes.